Pemanfaatan Digital Sebagai Upaya Untuk Meningkatkan Pemasaran Pandai Besi Rumbio Dengan Menggunakan Digital Marketing - Agus Sutikno; Tito Handoko; Angga Pramana; Yelmira Zalfiatri; Yelly Zamaya; Harsanto Mursyid (Lembaga Penelitian Pengabdian Kepada Masyarakat dan Dakwah Islamiyah Universitas Islam Kuantan Singingi, 2022)
Teratak Village is one of the villages that has a blacksmith center that focuses on the production of plantation harvesting equipment. The potential of the blacksmith business in Teratak village, Rumbio Jaya District is very interesting to be in Kembangan through devotion in utilizing digital technology. The use of websites, social media in this digital era websites are very important by business people to help the buying and selling process widely, easily, and as a means of promoting the potential of the village. The process of developing a blacksmith micro-business in the Teratak village of Rumbio Jaya District, Kampar Regency, experienced an incomprehension using technology and very limited capital. After conducting education and assistance in community service activities through the Abdimas integration KKN program, the community has the knowledge and ability to empower websites and social media to do Go digital marketing.